Do functional traits offset the effects of fragmentation? The case of large‐bodied diurnal lemur species. Issue 4 (3rd February 2020) - Eppley, Timothy M.; Santini, Luca; Tinsman, Jen C.; Donati, Giuseppe
Abstract: Primates worldwide are faced with increasing threats making them more vulnerable to extinction. Anthropogenic disturbances, such as habitat degradation and fragmentation, are among the main concerns, and in Madagascar, these issues have become widespread. As this situation continues to worsen, we sought to understand how fragmentation affects primate distribution throughout the island. Further, because species may exhibit different sensitivity to fragmentation, we also aimed to estimate the role of functional traits in mitigating their response. We collated data from 32 large‐bodied lemur species ranges, consisting of species from the families Lemuridae (five genera) and Indriidae (two genera). We fitted Generalized Linear Models to determine the role of habitat fragmentation characteristics, for example, forest cover, patch size, edge density, and landscape configuration, as well as the protected area (PA) network, on the species relative probability of presence. We then assessed how the influence of functional traits (dietary guild, home range size) mitigate the response of species to these habitat metrics. Habitat area had a strong positive effect for many species, and there were significantly negative effects of fragmentation on the distribution of many lemur species. In addition, there was a positive influence of PAs on many lemur species' distribution. Functional trait classifications showed that lemurs of all dietary guilds are negatively affected by fragmentation; however, folivore‐frugivores show greater flexibility/variability in terms of habitat area and landscape complexity compared to nearly exclusive folivores and frugivores. Furthermore, species of all home range sizes showed a negative response to fragmentation, while habitat area had an increasingly positive effect as home range increased in size. Overall, the general trends for the majority of lemur species are dire and point to the need for immediate actions on a multitude of fronts, most importantly landscape‐level reforestation efforts. Abstract : Heatmap showing the directional influence of various habitat metrics (F1: habitat area; F2: fragmentation; and F3: landscape complexity) and protected area metrics on the occurrence of diurnal and cathemeral lemur species belonging to the families Lemuridae and Indriidae. Empty boxes indicate variables that have been excluded after model selection. Species with no box are species for which the only‐intercept model scored best. Research Highlights: We assessed the role of habitat fragmentation on lemurs' relative probability of presence. Fragmentation negatively affected lemurs of all dietary guilds. Fragmentation and habitat availability negatively affected lemurs with larger home ranges.